2022
DOI: 10.32641/andespediatr.v93i2.3678
|View full text |Cite
|
Sign up to set email alerts
|

Debut de herpes zóster oftálmico como cefalea intensa

Abstract: El herpes zóster (HZ) es excepcional en la infancia y se define como la reactivación del virus varicela zóster latente, en pacientes que han pasado anteriormente la infección por varicela. Cuando afecta la rama oftálmica del trigémino se denomina herpes zóster oftálmico (HZO) pudiendo producir, entre otros síntomas, cefalea aguda, por lo que debe considerarse como diagnóstico diferencial.Objetivo: Describir un caso de HZO en un paciente pediátrico, reconocer sus características clínicas e importancia en el dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
0
0
Order By: Relevance
“…In some cases, however, HZO may start with headache (generalised or cluster), without the above prodromal symptoms. This was the case with our patient, and a few similar cases have been published to date, both in children and adults [7,8].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In some cases, however, HZO may start with headache (generalised or cluster), without the above prodromal symptoms. This was the case with our patient, and a few similar cases have been published to date, both in children and adults [7,8].…”
Section: Discussionsupporting
confidence: 85%
“…It is generally believed that the age and immune status predispose people to develop HZO and its sequelae, as well as affect their severity [12]. However, the paper by Campos et al [7], who reported HZO followed by postherpetic neuralgia and two severe flare-ups, in an immunocompetent 8-year-old girl, appears to demonstrate that it is not always the case. Similarly, the research suggests that the prevalence of HZO in females is higher than in males [13].…”
Section: Discussionmentioning
confidence: 99%